POSSIBLE ROLE OF PLATELET-MONOCYTE COMPLEXES IN THE PATHOGENESIS OF RECURRENT PREGNANCY LOSS - Oleg V. Pavlov; Sergei V. Chepanov; Ekaterina A. Kornyushina; Margarita O. Shengeliia; Daria V. Tkhai; Sergei A. Selkov (Медицинская иммунология, 2019)
Recurrent pregnancy loss is a significant clinical problem that affects 1-5% of the population, and in more than half of cases the cause of premature pregnancy loss remains unknown. One of the possible reasons is an imbalance in the maternal hemostatic system, leading to thrombosis of the uteroplacental vessels, decreased placental perfusion and hypoxia. Changes in the morphofunctional features of monocytes and the aggregates formed by them and activated platelets can be factors causing various complications of pregnancy, in particular, miscarriage. However, the role of platelet-monocyte complexes (PMC), which are of interest as a diagnostic marker and as a therapeutic target, is virtually unknown in the pathogenesis of recurrent pregnancy loss. The purpose of the study was to determine quantitative changes in the content and phenotypic characteristics of the peripheral blood PMC in patients with recurrent miscarriage, and to assess the effect of platelets on the expression of monocyte surface marker proteins during the physiological and pathological pregnancy. The study groups consisted of women aged 24-42 years diagnosed with recurrent miscarriage, having a current pregnancy of 6-12 weeks, and women with an uncomplicated (physiological) pregnancy of 7-12 weeks. In the total population and subpopulations of peripheral blood monocytes, the PMC content and expression of platelet and monocyte surface antigens CD62P, CD11b, CD86, CD162, HLA-DR, TREM-1 were determined using cytoflorimetric analysis. It was found that in recurrent pregnancy loss, the level of PMC was increased (26.5%) compared to uncomplicated pregnancy (15.3%), and all three subpopulations of monocytes (classical, intermediate and non-classical) contributed to the increase. At the same time, a decrease in HLA-DR expression and increase in CD11b expression was observed in the total PMC, while the expression of CD62P, CD162, CD86 and TREM-1 did not change significantly. Monocyte subpopulations differently contributed to the changes in the expression of activation markers associated with recurrent miscarriage, and the changes seen in subpopulations were not always evident in the toatl monocyte population. A comparison of PMC and free monocytes showed that changes in the surface phenotype of monocytes aggregated with platelets, were caused by both the influence of platelets and other factors. In cases of recurrent miscarriage, a platelet-induced increase in the adhesive properties of monocytes was observed, which was manifested in an increase in CD11b expression. In contrast, the decrease in the level of HLA-DR expression in monocytes was not associated with their interaction with platelets. The results obtained suggest that recurrent miscarriage is accompanied by an increase in the content of peripheral blood PMC and changes in the antigenic phenotype of platelet-associated and free monocytes, demonstrate the immunomodulatory effect of platelets, and also provide justification for the importance of determining the expression patterns of surface antigenic markers of PMC for diagnostic and therapeutic purposes.